The Development of Scrapbook Media to Increase Learning Interest at PPKN Learning Environment Materials - Azizah, Uswatun; Mahmudah, Masrurotul; Aisyah, Nurul (International Journal on Advanced Science, Education, and Religion, 2025)
The Learning media is used to bridge teachers in delivering material in class. Apart from using media effectively and efficiently, learning media can increase students' interest in learning. The aim of this research is to determine the development of scrapbook media in increasing interest in learning for class IV MINU Tri Bhakti At-Taqwa students. The type of research used by researchers is Research and Development (R&D). By using the ADDIE theory which consists of the stages Analysis (analysis), Design (design), Development (development), Implementation (implementation), Evaluation (evaluation). Judging from the level of feasibility of scrapbook media in this research, it is based on validation carried out by material experts, media experts and student responses. The material expert validation results obtained 91.8% in the "very valid" category. Furthermore, the media expert validation questionnaire obtained 96.8% in the "very valid" category. Based on student responses, they obtained 91.6% in the "very appropriate" category. From the research results, scrapbook media can foster students' interest in learning as seen from students' feelings of joy, interest, attention and activeness in asking questions in the learning process.